2003
DOI: 10.1103/physreve.67.031403
|View full text |Cite
|
Sign up to set email alerts
|

Structure of random monodisperse foam

Abstract: The Surface Evolver was used to calculate the equilibrium microstructure of random monodisperse soap froth, starting from Voronoi partitions of randomly packed spheres. The sphere packing has a strong influence on foam properties, such as E (surface free energy) and (average number of faces per cell). This means that random foams composed of equal-volume cells come in a range of structures with different topological and geometric properties. Annealing-subjecting relaxed foams to large-deformation, tension-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
157
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(168 citation statements)
references
References 28 publications
11
157
0
Order By: Relevance
“…The tetrakaidecahredon is a polyhedron that packs to fill space, approximates the structural features observed through experiment, nearly satisfies the minimum surface energy condition, and is often used for modeling low-density foams [30,32]. In addition, for the tetrakaidecahedral unit cell, the value of the dimensionless measure of total edge length per (unit volume) 1/3 for the unit cell is nearly identical to that observed for many random cellular structures [33], suggesting that the tetrakaidecahedral unit cell gives a good representation of the total edge length and can be used to model the specific surface area of random cellular structures such as the porous, CG scaffold. For an open-cell tetrakaidecahedron with edges of circular cross-section, the specific surface area is:…”
Section: Relationship Between Specific Surface Area and Pore Sizementioning
confidence: 73%
“…The tetrakaidecahredon is a polyhedron that packs to fill space, approximates the structural features observed through experiment, nearly satisfies the minimum surface energy condition, and is often used for modeling low-density foams [30,32]. In addition, for the tetrakaidecahedral unit cell, the value of the dimensionless measure of total edge length per (unit volume) 1/3 for the unit cell is nearly identical to that observed for many random cellular structures [33], suggesting that the tetrakaidecahedral unit cell gives a good representation of the total edge length and can be used to model the specific surface area of random cellular structures such as the porous, CG scaffold. For an open-cell tetrakaidecahedron with edges of circular cross-section, the specific surface area is:…”
Section: Relationship Between Specific Surface Area and Pore Sizementioning
confidence: 73%
“…The data reported in [54], [55], and [56] are insufficient to provide definitive p-vector distributions for either polycrystalline aluminum or soap foam structures. However, they are sufficient to clearly distinguish those structures from the Poisson-Voronoi one.…”
Section: P-vectorsmentioning
confidence: 99%
“…Matzke [54] carefully recorded p-vector data for 1000 soap bubbles in a foam, and Williams and Smith [55] reported p-vector data for 91 individual cells in an aluminum polycrystal. More recently, Kraynik et al [56] reported p-vector data to characterize over 1000 simulated monodisperse foam bubbles, and we have reported the distribution of p-vectors in a set of 269,555 grains in simulated grain growth microstructures [33].…”
Section: P-vectorsmentioning
confidence: 99%
“…The non-isotropic part of the effective macroscopic stress τ ij of a dry soap froth [31] is evaluated as…”
mentioning
confidence: 99%
“…A method for simulating the equilibrium microstructure of random soap froth with controlled cell-size distributions [31][32][33] employs molecular dynamics to generate dense packings of rigid spheres, which are used to produce Laguerre (weighted-Voronoi) tessellations. The tessellations are initial conditions for the Surface Evolver [34], which minimizes surface area given cell volume constraints.…”
mentioning
confidence: 99%